2021
DOI: 10.1016/j.isci.2021.102649
|View full text |Cite
|
Sign up to set email alerts
|

KEAP1 deficiency drives glucose dependency and sensitizes lung cancer cells and tumors to GLUT inhibition

Abstract: Mutant KEAP1 exposes a metabolic liability provoked by high cystine uptake KEAP1-NRF2-SLC7A11 axis drives glucose dependency KEAP1 mutant NSCLC tumors are sensitive to GLUT inhibitor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…Likewise, KEAP1-mutant lung cancer cells were shown to have higher levels of NRF2 and its downstream target SLC7A11. In addition, KEAP1 deficient lung tumors were shown to be sensitive to inhibition of glucose transporter 1 (GLUT1) due to their glucose dependency ( 30 ). Similarly, Wohlhieter et al.…”
Section: Ferroptosis Regulators In Lung Cancermentioning
confidence: 99%
“…Likewise, KEAP1-mutant lung cancer cells were shown to have higher levels of NRF2 and its downstream target SLC7A11. In addition, KEAP1 deficient lung tumors were shown to be sensitive to inhibition of glucose transporter 1 (GLUT1) due to their glucose dependency ( 30 ). Similarly, Wohlhieter et al.…”
Section: Ferroptosis Regulators In Lung Cancermentioning
confidence: 99%
“…Based on this protocol described above, we have successfully conducted thiol analysis in our recent publications ( Liu et al., 2020 ; Koppula et al., 2021 ). The RSD/CV for these analytes are typically below 15% for biological replicates, and under 5% for technical replicates.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…It is possible that the cell line was with low-expression of SLC7A11/SLC3A2 or was with wild-type KEAP1 gene if significant accumulation of cystine or GSSG weren’t shown upon glucose starvation. For more detail, please refer to our recent publications ( Liu et al., 2020 ; Koppula et al., 2021 ).…”
Section: Troubleshootingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, while SLC7A11 high cancer cells have stronger antioxidant capabilities and can survive and grow better under oxidative stress conditions, high cystine uptake in SLC7A11 high cancer cells also exposes a metabolic liability and renders these cells to be exquisitely vulnerable under glucose limiting conditions. Our very recent study further showed that KEAP1 -mutant lung cancer cells or tumors (which exhibit aberrant SLC7A11 expression due to constitutive activation of NRF2 transcription factor) are also more dependent on glucose for survival and more sensitive to glucose transporter (GLUT) inhibition than their wild-type counterparts, suggesting a therapeutic strategy to target this largely incurable cancer subtype [ 10 ].…”
mentioning
confidence: 99%